Design of synchronous reluctance motors with multiobjective optimization algorithms - Cupertino, Francesco; Pellegrino, Gianmario; Gerada, C. (Institute of Electrical and Electronics Engineers (IEEE), 2014)
The automatic design of Synchronous Reluctance (SyR) machines is considered in this paper by means of Finite Element Analysis and Multi-Objective Optimization Algorithms (MOOA). The research focuses on the design of the rotor geometry which is the key aspect of the SyR machine design. In particular, the performance of three popular MOOAs is analyzed and compared in terms of quality of the final design and computational time. A procedure to minimize the computational burden of the optimized design process is introduced and applied to a three layer and to a five layer rotors. Two prototypes demonstrate experimentally the feasibility of the design procedure.